2022
DOI: 10.3389/fphar.2022.1096984
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent advances in exosomes and allergic rhinitis

Abstract: Allergic rhinitis is a chronic inflammatory disease of nasal mucosa caused by the presence of IgE after exposure to allergens, characterized by nasal irritation, hypersecretion of the nasal passages and sneezing, which frequently occurs in children and adolescents. There has been an increase in allergic rhinitis over the past few years due to air pollution. Exosomes have been discovered to be nano-sized vesicles, which contain a wide range of substances, including proteins and nucleic acids, numerous studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Mammalian cells produce and secrete extracellular vesicles that contain a mix of proteins and nucleic acids. These vesicles are believed to play an intricate role in cell-to-cell communications [ 113 , 114 , 115 ]. The idea of using lipid bilayer membrane vesicles for the delivery of bioactive molecules to cells has been readily adopted by the drug delivery field of research [ 116 , 117 ].…”
Section: Principles Of Phage Displaymentioning
confidence: 99%
“…Mammalian cells produce and secrete extracellular vesicles that contain a mix of proteins and nucleic acids. These vesicles are believed to play an intricate role in cell-to-cell communications [ 113 , 114 , 115 ]. The idea of using lipid bilayer membrane vesicles for the delivery of bioactive molecules to cells has been readily adopted by the drug delivery field of research [ 116 , 117 ].…”
Section: Principles Of Phage Displaymentioning
confidence: 99%
“…Therefore, allergen-carrying dex may be important targets for AR immunotherapy (17,18). Since the diverse and complex mode of information transfer between dex and various cells may serve an integral role in the occurrence and progression of AR, dex engineered to carry anti-allergic drugs may have the potential to interrupt the allergic and immune processes underlying AR on a novel level (5,19).…”
Section: Role Of Dendritic Cell-derived Exosomes In Allergic Rhinitis...mentioning
confidence: 99%
“…When allergens enter the body, they are presented by dcs to cd4 T cells to trigger allergic inflammatory responses, leading to the activation and maturation of dcs (2,3). Exosomes are secreted during the maturation and differentiation of dcs in AR (4,5). However, almost all cells and not only dcs can produce exosomes (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was observed that MSC-sEV effectively mitigated ILC2-related allergic airway inflammation, potentially mediated by miR-146a-5p, thereby proposing MSC-sEV as a promising cell-free therapeutic approach for the management of allergic disorders . Exosomes could also lead to the occurrence and progression of allergic rhinitis …”
Section: Introductionmentioning
confidence: 99%